Respuesta :

-5x-3y=12

x-3y=-6

Solve x-3y=-6 for x

Add 3y to both sides

x-3y+3y=-6+3y

x= 3y-6

Substitute 3y-6 for x in -5x-3y=12

-5x-3y=12

-5(3y-6)-3y=12

Simplify both sides of the equation

-18y+30=12

Add -30 to both sides

-18y+30+-30=12+-30

-18y=-18

Divide both sides by -18

-18y/-18= -18/-18

y=1

Substitute 1 for y in x = 3y-6

x= 3y-6

x= (3)(1)-6

Simplify both sides of the equation

x= -3

Answer : B

                ( -3 , 1 )


I hope that's really help you Kris ! Have a great night .